解方程:8x -4.5÷0.2=16 3(x+30)=6x+30 3-(5-2x)=x+273x-(67-84x)-14=76 15-(7-5X)=2X(11-3X) X+(X+10)+(x+8)=36×3 11×(4-x)+15×(4-X)=30

来源:学生作业帮助网 编辑:作业帮 时间:2022/12/02 16:40:02
解方程:8x -4.5÷0.2=16 3(x+30)=6x+30 3-(5-2x)=x+273x-(67-84x)-14=76 15-(7-5X)=2X(11-3X) X+(X+10)+(x+8)=36×3 11×(4-x)+15×(4-X)=30

解方程:8x -4.5÷0.2=16 3(x+30)=6x+30 3-(5-2x)=x+273x-(67-84x)-14=76 15-(7-5X)=2X(11-3X) X+(X+10)+(x+8)=36×3 11×(4-x)+15×(4-X)=30
解方程:8x -4.5÷0.2=16 3(x+30)=6x+30 3-(5-2x)=x+2
73x-(67-84x)-14=76 15-(7-5X)=2X(11-3X) X+(X+10)+(x+8)=36×3 11×(4-x)+15×(4-X)=30

解方程:8x -4.5÷0.2=16 3(x+30)=6x+30 3-(5-2x)=x+273x-(67-84x)-14=76 15-(7-5X)=2X(11-3X) X+(X+10)+(x+8)=36×3 11×(4-x)+15×(4-X)=30
73x-(67-84x)-14=76 73x-(67-84x)=76+14 73x=90+67-84x 73x+84x=157 157x=157 x=1